Effect of Processing Techniques on the Quality and Acceptability of Young Carambola (Averrhoa carambola) Fruit Pickle - Yusof, Salmah; Vengrasalam, Kalaivani (Universiti Putra Malaysia Press, 1994)
The potential use of young carambola fruits for pickle production was studied using the conventional salt-stock and the blanching methods. Fruits Pickled were in the form of whole fruits and thick and thin slices. The suitability of each technique was graded based on the quality and acceptance of the final product. Samples for analysis were taken at different stages of processing and were analysed for ascorbic acid content, titratable acidity, and texture; and the final product was subjected to sensory analysis for evaluation on crunchiness, taste, flavour and size preference. There was no significant difference in the physical and chemical quality of products obtained from both methods but sensory evaluation showed that the blanched, thickly sliced pickle was preferred for its crunchiness. However, storage study showed that the blanched pickle became soft after 1 month. The water activity of the pickle was 0.94.